Temperature Analysis for Indoor Environmental Quality (IEQ) of UKM Architecture Studio - Nurakmal, Abdullah@ Goh Tuo Ho; Azalillah Ramdani, Musa; Che-Ani, A. I.; Norngainy, Mohd Tawil; Mazlan, Mohd Tahir (Elsevier Science, Ltd., 2012)
Indoor environmental quality (IEQ) plays an important role in ensuring the conducive studio-based learning environment for architecture students. This paper looks into one of the IEQ parameter namely temperature condition in an architecture studio. Being centralized air-conditioning at all times, the temperature range is very much important throughout the day since the students are learning, discussing and relaxing in the studio. The methodology adopted is two-fold. First by measuring the temperature using the equipment named LM-8100, and second by questionnaire survey in gauging the temperature comfort and humidity level from students’ perspective. Temperature reading is taken for 11-hours in 2 days. The IEQ matrix is developed to analyze these 2 parameters concurrently, that also useful to conclude this study. The finding shows that the temperature setting is not within the range of MS 1525:2007. But interestingly, the students perceived it as normal and do not hinder them to stay longer inside their studio. This is somehow good to the learning environment for short term, but in the long run might give negative health effect to the students.